A high‐throughput approach to predict A‐to‐I effects on RNA structure indicates a change of double‐stranded content in noncoding RNAs. Issue 5 (24th September 2022) - Delli Ponti, Riccardo; Broglia, Laura; Vandelli, Andrea; Armaos, Alexandros; Burgas, Marc Torrent; Sanchez de Groot, Natalia; Tartaglia, Gian Gaetano
Abstract: RNA molecules undergo a number of chemical modifications whose effects can alter their structure and molecular interactions. Previous studies have shown that RNA editing can impact the formation of ribonucleoprotein complexes and influence the assembly of membrane‐less organelles such as stress granules. For instance, N6‐methyladenosine (m6A) enhances SG formation and N1‐methyladenosine (m1A) prevents their transition to solid‐like aggregates. Yet, very little is known about adenosine to inosine (A‐to‐I) modification that is very abundant in human cells and not only impacts mRNAs but also noncoding RNAs. Here, we introduce the CROSSalive predictor of A‐to‐I effects on RNA structure based on high‐throughput in‐cell experiments. Our method shows an accuracy of 90% in predicting the single and double‐stranded content of transcripts and identifies a general enrichment of double‐stranded regions caused by A‐to‐I in long intergenic noncoding RNAs (lincRNAs). For the individual cases of NEAT1, NORAD, and XIST, we investigated the relationship between A‐to‐I editing and interactions with RNA‐binding proteins using available CLIP data and catRAPID predictions. We found that A‐to‐I editing is linked to the alteration of interaction sites with proteins involved in phase separation, which suggests that RNP assembly can be influenced by A‐to‐I. CROSSalive is available at http://service.tartaglialab.com/new_submission/crossalive .